Boron water quality for the Plynlimon catchments - C. Neal (Hydrology and Earth System Sciences, 1997)
Boron concentrations in rainfall, throughfall and stemflow for Spruce stands, mist, streamwater and groundwater are compared with chloride to assess atmospheric sources and catchment input-output balances for the Plynlimon catchments. In rainfall, boron concentration averages about 4.5 μg-B l-1 and approximately two thirds of this comes from anthropogenic sources. In through-fall and stemflow, boron concentrations are approximately a factor of ten times higher than in rainfall. This increase is associated with enhanced scavenging of mist and dry deposition by the trees. As the sampling sites were close to a forest edge, this degree of scavenging is probably far higher than in the centre of the forest. The throughfall and stemflow concentrations of boron show some evidence of periodic variations with time with peak concentrations occurring during the summer months indicating some vegetational cycling. In mist, boron concentrations are almost twenty times higher than in rainfall and anthropogenic sources account for about 86% of this. Within the Plynlimon streams, boron concentrations are about 1.4 to 1.7 times higher than in rainfall. However, after allowance for mist and dry deposition contributions to atmospheric deposition, it seems that, on average, about 30% of the boron input is retained within the catchment. For the forested catchments, felling results in a disruption of the biological cycle and a small increase in boron leaching from the catchment results in the net retention by the catchment being slightly reduced. Despite the net uptake by the catchment, there is clear evidence of a boron component of weathering from the bedrock. This is shown by an increased boron concentration in a stream influenced by a nearby borehole which increased groundwater inputs. The weathering component for boron is also observed in Plynlimon groundwaters as boron concentrations and boron to chloride ratios are higher than for the streams. For these Goundwaters, increases in boron concentrations are matched linearly by increases in the concentration of the principal ase cation weathering component in the bedrock, calcium. However, the bedrock weathering term is not uniform as the ratio of boron to calcium concentration varies for the different boreholes sampled.